Prism adaptation changes the subjective proprioceptive localization of the hands. Issue 1 (23rd November 2013) - Scarpina, Federica; Van der Stigchel, Stefan; Nijboer, Tanja Cornelia Wilhelmina; Dijkerman, Hendrik Christiaan
<x xml:space="preserve">Abstract</x> Prism adaptation involves a proprioceptive, a visual and a motor component. As the existing paradigms are not able to distinguish between these three components, the contribution of the proprioceptive component remains unclear. In the current study, a proprioceptive judgement task, in the absence of motor responses, was used to investigate how prism adaptation would specifically influences the felt position of the hands in healthy participants. The task was administered before and after adaptation to left and right displacing prisms using either the left or the right hand during the adaptation procedure. The results appeared to suggest that the prisms induced a drift in the felt position of the hands, although the after‐effect depended on the combination of the pointing hand and the visual deviation induced by prisms. The results are interpreted as in line with the hypothesis of an asymmetrical neural architecture of somatosensory processing. Moreover, the passive proprioception of the hand position revealed different effects of proprioceptive re‐alignment compared to active pointing straight ahead: different mechanisms about how visuo‐proprioceptive discrepancy is resolved were hypothesized.